Innovations in Sports: A Key to Enhancing Rehabilitation Outcomes - Osuch, Dobromiła; Anderska, Agnieszka; Błachnio, Klaudia; Opala, Dominika; Szczotka, Dominika; Drabik, Aleksandra; Staszczyk, Izabela; Szemplińska, Antonina; Chernysh, Anna Maria (Quality in Sport, 2024)
Introduction and purpose: Traditional rehabilitation methods often have limitations in improving motor function and cognitive abilities. This review aims to provide an updated overview of innovative methods in rehabilitation, focusing on the role of immersive and interactive technologies in enhancing rehabilitation outcomes. The literature suggests that these technologies can improve upper limb mobility, grip strength, and manual dexterity, as well as cognitive function, attention, and spatial awareness. Additionally, innovative balance and gait rehabilitation programs have been shown to improve functional mobility and reduce the risk of falls. The use of these technologies in combination with other rehabilitation modalities, such as electrostimulation and robotic assistance, may lead to even greater improvements in motor function and cognitive abilities. While more research is needed to fully understand the benefits and limitations of these innovative approaches, the existing evidence suggests that they have the potential to revolutionize rehabilitation and improve quality of life for patients. Materials and Methods: A literature review was conducted using PubMed with search phrases immersive and interactive technologies and rehabilitation. Description of the state of knowledge: Traditional rehabilitation methods often have limitations in improving motor function and cognitive abilities.Upper extremity impairment is a common and debilitating consequence of stroke. Summary: imersive and interactive technologies have the potential to improve upper limb mobility, grip strength, and manual dexterity, as well as cognitive function, attention, and spatial awareness. Innovative balance and gait rehabilitation programs have been shown to improve functional mobility and reduce the risk of falls. The use of these technologies in combination with other rehabilitation modalities may lead to even greater improvements in motor function and cognitive abilities.